2020
DOI: 10.1055/s-0039-1700987
|View full text |Cite
|
Sign up to set email alerts
|

Primary Umbilical Endometriosis in an Adolescent Girl: Unsuspected Pathology

Abstract: Endometriosis affects 7 to 10% of women of reproductive age. Primary umbilical endometriosis (PUE) is even rarer with unclear pathogenesis. We report a case of PUE possibly the youngest patient reported in the literature.A 16-year-old girl of African origin presented with painful umbilical lump for 2 to 3 months duration with background history of precocious puberty, cyclical vomiting, and menorrhagia. Clinical examination showed dark-colored, tender, irreducible umbilical lump. A provisional diagnosis of inca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In a review of PUE literature published during the period 2015-2020, seventeen studies were identified written in English or French language (Table 1) [9,13,[22][23][24][26][27][28][29][30][31][32][33][34][35][36][37]. Based on all reports, the mean age of patients with PUE was 36.3 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of PUE literature published during the period 2015-2020, seventeen studies were identified written in English or French language (Table 1) [9,13,[22][23][24][26][27][28][29][30][31][32][33][34][35][36][37]. Based on all reports, the mean age of patients with PUE was 36.3 years.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between primary and secondary UE appears important from a pathogenic perspective [ 13 , 14 ]. Over time, the following theories for UE have been developed: (a) migration of refluxed endometrial cells through the abdominal cavity; (b) dissemination of endometrial cells through the lymphatic system; (c) embryonic remnants in the umbilical fold (e.g., the urachus and umbilical vessels) [ 8 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many journals (e.g., European Journal of Pediatric Surgery Reports ) do not use the standard subheadings (i.e., Introduction, Methods, Results, and Discussion referred to as IMRaD) in the abstract. 8 9 However, other journals encourage IMRaD even in the abstract. Thus, consult the “Instructions for Authors” of the target journal before you write the abstract.…”
Section: Introductionmentioning
confidence: 99%